Intra and inter sentential code switching in Malay songs - Wan Nur Syaza Sahira Wan Rusli; Azianura Hani Shaari (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
Code switching and code mixing have been across a variety of languages, but little is known about why they are used as communicative strategies for entertainment. This study is an attempt to fill in this gap by exploring and describing the recent phenomenon of English code-switching in Malay songs. Based on Poplack’ Theory (1980), this study discovered two types of code switching used in Malay songs; intrasentential and intersentential code switching. The classification of the code-switching functions was based on Appel and Musyken (2006) six functions of code switching and supplemented by Nur Syazwani Halim and Marlyna Maros (2014), Oreoluwa (2013), and Bullock and Toribio (2009). Based on Appel and Musyken (2006), expressive function was found to be the most famous function whereas metalinguistic function was the least function used. Also, the findings indicated that phatic function was more suitable for intrasentential code switching and metalinguistic function was more appropriate for intersentential code switching.